Implementation of Islamic Religious Education Using Fun Learning at Primary Schools - Sartika, Diah; Tanjung, Ellisa Fitri; Nurzannah, Nurzannah (Southeast Asian Journal of Islamic Education, 2024)
Fun learning aims to create a fun and interactive learning atmosphere so students are more motivated and actively involved in the learning process. This study aims to examine the implementation of Islamic Religious Education (PAI) learning using the fun learning method and the ability of teachers to apply the proper learning method in delivering learning in public elementary schools. This study used a qualitative method with a descriptive-analytical approach. Research data were obtained from two PAI teachers and three students through interviews, observations, and documentation as primary data sources. The results of the study indicate that the implementation of Islamic Religious Education (PAI) learning with the fun learning method in public elementary schools is carried out with various strategies applied, namely the use of interactive learning media, educational games, direct practice, group activities, stories, dramas, outdoor activities, awards and motivation and integration of Islamic values in daily activities. The ability of teachers to apply the proper learning method in delivering learning is influenced by several factors: understanding student characteristics, mastery of learning materials, creativity and innovation in learning, the ability to use educational technology, flexibility in using various methods, classroom management skills, evaluation skills and reflection and involvement in professional development. The implications of this research show that fun learning has great potential to improve the quality of Islamic Religious Education learning in elementary schools.